The technology we choose to create: Human rights advocacy in the Internet Engineering Task Force - Cath, C (Elsevier, 2021)
This article is an ethnographic analysis of recent efforts in the Internet Engineering Task Force (IETF) to consider human rights values in the development of Internet networking standards and protocols. By deploying qualitative methods—65 semi-structured interviews and two years of ethnography—I provide a detailed anthropological picture of how IETF participants understand technology, and what consequences their perspectives have for human rights advocacy. Internet governance scholars have recently debated the “turn to the infrastructure” and the role of human rights advocacy in the IETF. Bringing these insights together, I argue that the IETF's shared view about the non-prescriptive nature of technology encourages participants to resist the inclusion of human rights values through standardization. I identify this non-prescriptive view of technology as a barrier to addressing human rights through direct civil society engagement in standardization organizations. This view explains why standards rarely reflect human rights concerns as a contextually embedded and social issue more than a technological or communicative problem. My findings inform ongoing academic and policy debates about the role of human rights advocates in the IETF and provide an epistemic grounding for the recent “turn to the infrastructure” in Internet governance research.